Development of an approach based on historical Landsat data for delineating Canadian flood zones at different return periods - Chokmani, Karem; Zidi, Haythem; El Alem, Anas; Gill-Fortin, Jasmin (EGU General Assembly Conference Abstracts, 2024)
The study addresses the need for flood risk anticipation and planning, through the development of a flood zone mapping approach for different return periods, in order to best prevent and protect populations. Today, traditional methods are too costly, too slow or require too many requirements to be applied over large areas. As part of a project funded by the Canadian Space Agency, Geosapiens and the Institut National de la Recherche Scientifique set themselves the goal of designing an automatic process to generate water presence maps for different return periods at a resolution of 30 m, based on the historical database of Landsat missions from 1982 to the present day. This involved the design, implementation and training of a deep learning algorithm model based on the U-Net architecture for the detection of water pixels in Landsat imagery. The resulting maps were used as the basis for applying a frequency analysis model to fit a probability of occurrence function for the presence of water at each pixel. The frequency analysis data were then used to obtain maps of water occurrence at different return preiods such as 2, 5 and 20 years.

How Ice Mapping Can Help Manage and Prevent Ice Jams: Remote Sensing Monitoring of the Saint-François River, Québec - Plante Lévesque, Valérie; Persent, Marc-Antoine; Lhissou, Rachid; Chokmani, Karem; Gauthier, Yves; Bernier, Monique (Canadian Journal of Remote Sensing, 2024)
Keywords: Infolettre; Infolettre_Octobre_2024